2021
DOI: 10.1103/physrevlett.127.051801
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Zbb¯ Couplings: From LEP to LHC

Abstract: The bottom quark forward-backward asymmetry (A b F B ) data at LEP exhibits a long-standing discrepancy with the standard model prediction. We propose a novel method to probe the Zb b interactions through gg → Zh production at the LHC, which is sensitive to the axial-vector component of the Zb b couplings. We demonstrate that the Zh data collected at the 13 TeV LHC can already resolve the apparent degeneracy of the anomalous Zb b couplings implied by the LEP precision electroweak measurements, with a strong de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Here, we focus on the parameter space with κ V,A > 0, since the off Z-pole A b F B measurements have excluded the region with κ V,A < 0 [4]. In the same figure, we also show the constraints from the R b (blue region) and (A b FB , A b ) (red region) measurements at the Z-pole, as well as the expected constraint from the measurement of the gg → Zh production at the HL-LHC (gray region) [8]. To derive the expected constraint from the gg → Zh measurement, we have taken into account a factor of 2, as compared to that presented in Ref.…”
Section: The Zb B Anomalous Couplingsmentioning
confidence: 80%
See 3 more Smart Citations
“…Here, we focus on the parameter space with κ V,A > 0, since the off Z-pole A b F B measurements have excluded the region with κ V,A < 0 [4]. In the same figure, we also show the constraints from the R b (blue region) and (A b FB , A b ) (red region) measurements at the Z-pole, as well as the expected constraint from the measurement of the gg → Zh production at the HL-LHC (gray region) [8]. To derive the expected constraint from the gg → Zh measurement, we have taken into account a factor of 2, as compared to that presented in Ref.…”
Section: The Zb B Anomalous Couplingsmentioning
confidence: 80%
“…To derive the expected constraint from the gg → Zh measurement, we have taken into account a factor of 2, as compared to that presented in Ref. [8], to include both the ATLAS and CMS contributions, which results in a factor of √ 2 reduction in its error band size. The similar results, but for the 100 TeV pp collider, are shown in Fig.…”
Section: The Zb B Anomalous Couplingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Breaking the above-mentioned degeneracy and as well as confirming or excluding the anomaly of A b FB measurement at LEP is one of the major tasks of the particle physics at the current and future colliders. Recently, we demonstrated that the axial-vector component of Zb b coupling can be determined by the precision measurement of gg → Zh production at the Large Hadron Collider (LHC) and the high-luminosity LHC (HL-LHC) [6], while its vector component can be better constrained by the measurement of single-spin asymmetry (SSA) in the polarized leptonhadron collisions, such as at HERA and the upcoming Electron-Ion Collider (EIC) [7].…”
Section: Introductionmentioning
confidence: 99%